(untitled) (Journal of the Bangladesh Agricultural University, 2024)
The agriculture sector is constantly adopting environmentally friendly and sustainable methods to reduce the harmful effects of herbicides on crop production. In this respect, an experiment was conducted at the Agronomy Field Laboratory (AFL), Bangladesh Agricultural University (BAU), Mymensingh to assess the allelopathic effects of grass pea crop residues on weed suppression and the growth performance of Boro rice from December 2021 to May 2022. The experiment consisted of four cultivars of Boro rice i.e. BAU dhan3, BRRI dhan28, BRRI dhan81, BRRI dhan96 along with four different treatments of weed control viz. no extract and no weeding (control), hot water extract of Grass pea residues as pre-emergence application at 3 DAT (days after transplanting), hot water extract of Grass pea residues as pre-emergence application at 3 DAT+ post- emergence at 10 DAT, hand weeding 3 times at 15, 30 and 45 DAT. The highest weed growth was noticed when no extract was added and the lowest was found when three times hand weeding was performed. The highest number of effective tillers (NET) hill-1, number of spikelets panicle-1 (NSP) and grain yield (GY), straw yield (SY) and biological yield (BY) were recorded from the rice variety BAU dhan3. The highest NET hill-1, NSP, 1000-grain weight (TGW), GY, SY and BY were recorded from three hand weeding which was followed by hot water extract of grass pea as pre-emergence application at 3 DAT+ post-emergence application at 10 DAT. From the interaction it is observed that the highest NET hill-1, NSP, SY and BY were obtained from BAU dhan3 with three hand weeding which was followed by BAU dhan3 with hot water extract of grass pea as pre-emergence application at 3 DAT+ post-emergence application at 10 DAT. The findings of this study reveal that hand weeding, followed by the application of grass pea crop residues, effectively suppresses weed growth. Our research suggested leveraging the allelopathy-weed inverse relationship to address weed problems. This approach holds significant promise for weed management in the twenty-first century. J Bangladesh Agril Univ 22(3):360-368, 2024